(untitled) (International Journal of Engineering and Computer Science, 2017)
Healthcare environments today have turned to be technology-oriented. Also mobile devices and their usage has increased manifold in recent times. This paper presents the design and development of Android mobile application for patient healthcare. A body area network is a wireless network of biomedical sensors that are around to a human body. The aim of wireless body area network (WBAN) is to facilitate continuous recording and monitoring of a person’s health condition and transfer it over a long-distance communication network. The parameters sensed by the individual devices are to be transferred onto a mobile phone or a tablet via wireless network. This data is then gathered, stored, check for threshold and then sent to the physician for continuous monitoring of the patient’s health condition. The physician can thus access the patient’s health status on the go and this will help the patient to get immediate attention in life-threatening situations.